SECOND INSTAGRAM ACCOUNTS AS AN ALTERNATIVE EXPRESSION SPACE FOR GENERATION Z MEN (A STUDY OF USERS IN RW 13 TEBET, SOUTH JAKARTA) - Ery Farida; RR Roosita Cindrakasih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The rapid growth of social media has encouraged the emergence of Instagram second accounts as alternative spaces for self-expression, particularly among Generation Z men who continue to experience social expectations related to masculinity. This study aims to examine how Generation Z men in RW 13 Tebet, South Jakarta, use Instagram second accounts as alternative spaces for self-expression. The research employed a qualitative approach with a phenomenological method. Informants were selected through purposive sampling and consisted of three active Instagram second account users and one triangulation informant. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. The findings reveal that second accounts function as private spaces where users freely express emotions, personal experiences, opinions, interests, and daily activities that are rarely shared on their main accounts. Participants reported feeling safer because their audiences were limited to trusted individuals, reducing social pressure and fear of negative judgment. From Erving Goffman's dramaturgical perspective, the main account represents the front stage, while the second account functions as the backstage where users present more authentic identities. This study concludes that Instagram second accounts serve not only as backup accounts but also as digital identity management strategies that support emotional well-being among Generation Z men.